Comparison of the efficacy of intralesional versus intramuscular injection Meglumine Antimoniate in the treatment of sores of Cutaneous Leishmaniasis - Tareen, Attiya; Ahmad, Syed Afaq; Khan, Ikramullah (International Journal of Pathology, 2018)
To compare the efficacy of intralesional with intramuscular injection meglumine antimoniate in the treatmentof Cutaneous Leishmaniasis.Design: Prospective, comparative, interventional study.Setting: Pakistan Institute of Medical Sciences, [PIMS] Islamabad.Material and Methods: Seventy six (40 males, 36 females) consecutive patients with sores of Cutaneous Leishmaniasispresenting to the Dermatology department, underwent treatment with Intralesional (1 ml/cm2 of Sb) or Intramuscularinjection Meglumine antimoniate ((20 mg Sb/kg/day for 21 to 28 days) according to the selection criteria for each group fromApril 2004 to March 2005. On the basis of demonstration of Leishmania tropica (LT) bodies in the skin slit smears/skinbiopsies, 76 patients were included in the study and were followed-up for therapeutic safety and efficacy at different intervals.After completing local or systemic treatment, cure rate was calculated by observing the improvement criteria i.e. flattening,softening, decrease in size of lesion and absence of erythema, induration, . According to the sample selection procedure for thetwo modalities of treatment 46 (60.5%) patients were found suitable for Intralesional therapy and 30(39.5%) were foundsuitable for Intramuscular therapy.Results: Males 40(52.6%) constituted a slightly greater number than females 36(47%) The final outcome of intralesionalinjection meglumine antimoniate at weekly intervals in 46 patients was that 44 (95.65%) got completely cured, whereas amongthose receiving I/M therapy 25(83.3%) got cured with their lesions getting almost flattened and itch/pain subsided. Z test forproportion was used for comparison which was Z=1.75 showing that proportion of cured patients with IL treatment wasgreater than IM treatment (P= 0.027 =<0.05) which confirms that there is a significant relationship between route ofadministration and outcome of lesion .The average number of injections required for 1/L was found to be 6 at weeklyintervals and 18 for 1/M treatment. Both the treatments were given according to the recommended guidelines of WHO.Design: Prospective, comparative, interventional study.Conclusion: Intralesional therapy is superior to Intramuscular therapy with meglumine antimoniate in terms of efficacy,safety, outcome